Pewarnaan Pelangi Antiajaib pada Amalgamasi Graf - Riniatul Nur Wahidah; Dafik Dafik; Ermita Rizki Albirri (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2022)
Let $G$ is a connected graph with vertex set $V(G)$ and edge set $E(G)$. The side weights for $uv\in E(G) $ bijective function $f:V(G)→\{1,2,…, |V(G)|\}$ and $ w(uv)= f(u)+f(v) $ . If each edge has a different weight, the function $f$ is called an antimagic edge point labeling. Is said to be a rainbow path, if a path $P$ on the graph labeled vertex $G$ with every two edges $ ,u'v'\in E(P) $ fulfill $ w(uv)≠ w(u'v') $. If for every two vertices $u,v \in V(G)$, their path $uv$ rainbow, $f$ is called the rainbow antimagic labeling of the graph $G$. Graph G is an antimagic coloring of the rainbow if we for each edge $uv$ weight color side $w(uv)$. The smallest number of colors induced from all sides is the rainbow antimagic connection number $G$, denoted by $rac(G)$. This study shows the results of the rainbow antimagic connection number from amalgamation graph.